2012
DOI: 10.1103/physreve.86.016308
|View full text |Cite
|
Sign up to set email alerts
|

Optimal energy-utilization ratio for long-distance cruising of a model fish

Abstract: The efficiency of total energy utilization and its optimization for long-distance migration of fish have attracted much attention in the past. This paper presents theoretical and computational research, clarifying the above well-known classic questions. Here, we specify the energy-utilization ratio (f(η)) as a scale of cruising efficiency, which consists of the swimming speed over the sum of the standard metabolic rate and the energy consumption rate of muscle activities per unit mass. Theoretical formulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 21 publications
(30 reference statements)
0
12
0
Order By: Relevance
“…It can, for instance, be used to compare the efficiency of man-made systems and biological ones. It can ot, however, be used to compare or optimize the performance of hull or body shapes (Kagemoto, 2013;van Rees et al, 2013), or swimming velocities (Liu et al, 2012).…”
Section: Optimizing Velocity and Body Shapementioning
confidence: 99%
See 1 more Smart Citation
“…It can, for instance, be used to compare the efficiency of man-made systems and biological ones. It can ot, however, be used to compare or optimize the performance of hull or body shapes (Kagemoto, 2013;van Rees et al, 2013), or swimming velocities (Liu et al, 2012).…”
Section: Optimizing Velocity and Body Shapementioning
confidence: 99%
“…This difficulty can easily be overcome by adding a cost to time. From a biological point of view, P in can be replaced by the total power P t defined in Liu et al (2012) as:…”
Section: Optimizing Velocity and Body Shapementioning
confidence: 99%
“…In this manner, w e analyze the primary flow features around fish bodies. It is quite pertinent to mention that since fish schooling involves complex interaction not only w ith the other bodies but also w ith flow itself in lateral/transversal directions, 2D investi-gations can serve as an appropriate choice to start hydrodynamic analysis and quantification of the flow characteristics [9,12,27,28]. For comparison, it is also important to mention the conclusions draw n by L iu et al [29,30] through numerical simulations over a sw imming tadpole.…”
Section: Introductionmentioning
confidence: 99%
“…Authors also noticed that the energy-utilization ratio, which was proposed by Liu et al [32], might be another choice for calculating the propulsive efficiency. It has been found that this may cause slight changes in the efficiency magnitude, however, the overall conclusions of this paper remain unaffected.…”
Section: Fig 3 (A)mentioning
confidence: 97%